Peningkatan Kesadaran Masyarakat Untuk Membayar Pajak Melalui Program Sosialisasi Perpajakan Desa - Akbar Fauzan; Santy Fitnawati WN; Irmayanti Irmayanti (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Discussing taxation, taxes have a very urgent position in the discussion of state life. The reason is that tax funds are really needed to finance the majority of expenditure for state development so that it is hoped that it will bring prosperity to the community. This research was conducted to determine the role of disseminating knowledge about taxation which is important in providing tax payments to the public. The research method is to use qualitative with descriptive analysis, namely library research. Then sources of scientific articles and related books and newspapers about taxpayers. The results of this research are that tax awareness, tax awareness and the consequences of taxation have a positive effect on taxpayer compliance.